The management of children with atopic dermatitis. An important goal for all pediatricians. - Frati, F. (European Journal of Pediatric Dermatology, 1998)
The Author reviews the role of the pediatrician in the management of atopic dermatitis, particularly the early diagnosis, environmental prevention, dietetic treatment, knowledge of cosmetic products besides drugs, evaluation of the treatment costs, educational programs and, finally, quality of life (Presented in the International Congress of Neonatal Dermatology - Bari - Italy, September 24-27, 1998).